2008
DOI: 10.1901/jeab.2008.90-313
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Resurgence and Behavioral History

Abstract: The contribution of past experiences to concurrent resurgence was investigated in three experiments. In Experiment 1, resurgence was related to the length of reinforcement history as well as the reinforcement schedule that previously maintained responding. Specifically, more resurgence occurred when key pecks had been reinforced on a variable-interval 1-min schedule than a variable-interval 6-min schedule, but this effect may have been due either to the differential reinforcement rates or differential response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
96
2
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(124 citation statements)
references
References 27 publications
15
96
2
6
Order By: Relevance
“…3 adequately describes the repeated-resurgence phenomenon, although considerable variability occurred in the individual parameter estimates. It is important to note that decreased resurgence across tests is not contradictory to previous findings that repeated examinations of resurgence within subjects result in similar relapses (da Silva, Maxwell, & Lattal, 2008; Lieving & Lattal, 2003), because in these previous experiments baseline responding was reestablished before the second examination of extinction and resurgence. In these cases, Eq.…”
Section: Discussioncontrasting
confidence: 54%
“…3 adequately describes the repeated-resurgence phenomenon, although considerable variability occurred in the individual parameter estimates. It is important to note that decreased resurgence across tests is not contradictory to previous findings that repeated examinations of resurgence within subjects result in similar relapses (da Silva, Maxwell, & Lattal, 2008; Lieving & Lattal, 2003), because in these previous experiments baseline responding was reestablished before the second examination of extinction and resurgence. In these cases, Eq.…”
Section: Discussioncontrasting
confidence: 54%
“…Although studies about the role of reinforcers rate on the reappearance of a response have inconsistent results (e.g., Craig & Shahan, 2016;Podlesnik & Shahan, 2010;Silva et al, 2008), both in Experiment 1 and Experiment 2 of the present study the reappearance of S1 was correlated to higher rate of reinforcers. Moreover, the number of responses per sequence or, more precisely, the intrasequence discriminative control, which is stronger in sequences with lower number of responses (Abreu- Rodrigues et al, 2004), should also be considered.…”
Section: Discussioncontrasting
confidence: 68%
“…However, attributing the more frequent reappearance of S1 with high probability to the higher rate of reinforces for that sequence demands care, since the contribution of the rate of reinforcers to resurgence is a controversial issue in literature. Some authors (e.g., Craig & Shahan, 2016;da Silva, Maxwell & Lattal, 2008) advocate that the rate of reinforcers is not a reliable predictor of resurgence or, at least, as reliable as the rate of responses (here, the rate of sequences did not vary between groups or contexts). Other authors (e.g., Podlesnik & Shahan, 2010), however, suggest a direct relation between rate of reinforcers and magnitude of resurgence.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few exceptions exist in which animals were required to abstain from responding to earn reinforcers during Phase 2. For example, experiments have shown that resurgence can occur when alternative reinforcement is delivered according to a differential-reinforcement-of-other-behavior (DRO) schedule (da Silva, Maxwell, & Lattal, 2008; Doughty, da Silva, & Lattal, 2007; Pacitti & Smith, 1977). According to this schedule, reinforcers during Phase 2 are delivered independent of responding on an explicit R2.…”
Section: Evaluating the Theoriesmentioning
confidence: 99%